Evangelism Bridge to Parmalim Believe System Based on Acts 17:23: Jembatan Penginjilan kepada Aliran Kepercayaan Parmalim Berdasarkan Kisah Para Rasul 17:23 - Molsen Siburian; Stimson Hutagalung; Rolyana Ferinia (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2022)
The Parmalim belief, which is the original religion of the Batak tribe, is often ignored and even considered as sipelebegu (worshipping ancestral spirits). On the one side, Parmalim has teachings that are similar to the Bible, so it becomes a challenge in itself to convey the message of the Gospel to the Parmalim community. So the purpose of this paper is to find a concept of evangelism without mocking and demeaning, instead showing sincere sympathy and respect for their beliefs by using similar teachings as a bridge in this evangelism. The formulation of the problem that will be a reference in this writing, namely, what are the teachings taught in the Parmalim belief? Do Parmalim's teachings have anything in common with the teachings in the Bible? What is Paul's method in Acts. 17:23 can be applied in this context? The method used is a qualitative method with data collection through literature studies, articles or related journals. The result is that the teachings of worship on Saturdays, the prohibition of eating blood, pigs and dogs can be used as a bridge to convey the gospel message according to Paul's concept in Acts 17:23, namely an approach without appreciating judgment.